PENGARUH KEPEMIMPINAN, KOMPETENSI, BEBAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI LEMBAGA LAYANAN PENDIDIKAN TINGGI (LLDIKTI) WILAYAH III JAKARTA - Sufyati HS, Sufyati HS; Risa, Mila (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This research aims to analyze and determine the influence of leadership, competence, workload, and work environment on employee performance of The Higher Education Services Agency Region III Jakarta. Design/methodology/approach- A sample of 71 participants was intentional with purposive sampling. Multiple linear regression is used to test the hypothesis. Findings- The results showed that leadership, competence, and work environment positively and significantly affect the employee's performance, while the workload negatively and significantly impacted the employee's performance. Implication- In efforts to improve employee performance, institutions need to pay attention and know what is the problem as a basis for correcting weaknesses and maintaining strengths through the implementation of leadership, competence, workload, and work environment properly Keywords: Leadership, competence, workload, work environment, and performance.